IMPROVING STUDENT LEARNING OUTCOMES BY USING THE NUMBERED HEAD TOGETHER (NHT) LEARNING MODEL IN THE SUBJECTS OF THE APPLICATION OF ELECTRONIC CIRCUITS (PRE) KELAS XI TAV SMK NEGERI 1 MANDAU TAHUN PELAJARAN 2019 / 2020 - Irda Nelli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This study aims to improve students' learning outcomes in the subjects of Electronic Circuit Application with the learning model